Species richness pattern of aquatic vascular macrophytes along elevation gradients in Nepal Himalayas - ELIZA ACHARYA SIWAKOTI; BABURAM NEPALI; TEJ NARAYAN MANDAL; CHITRA BAHADUR BANIYA (Society for Indonesian Biodiversity, 2023)
Abstract. Siwakoti EA, Nepali B, Mandal TN, Baniya CB. 2023. Species richness pattern of aquatic vascular macrophytes along elevation gradients in Nepal Himalayas. Biodiversitas 24: 5179-5190. Aquatic vascular macrophytes constitute an important component of aquatic ecosystems. This study aims to determine the species richness pattern of aquatic vascular macrophytes along elevation gradients (100-4900 m asl) in the Nepal Himalayas. We used available published literature on elevational ranges of aquatic vascular macrophytes in Nepal to interpolate the species elevational ranges, thereby providing species richness estimates for 100 m elevational bands. A total of 113 species of aquatic vascular macrophytes belonging to 66 genera under 35 families were recorded from Nepal. Among these macrophytes, dicots were represented by 21 families, monocots with 10 families and pteridophytes with 4 families. Regarding the geographical divisions, the total number of aquatic vascular macrophytes recorded was 76 from the east, 90 from the central and 67 from the west, conclusively central Nepal showed the maximum number of macrophytes. The highest species richness was contributed by Hydrocharitaceae followed by Potamogetonaceae, Plantaginaceae, Lentibulariaceae and Nymphaeaceae. So far, the functional types of macrophytes are concerned, free-floating species were 15, submerged species were 36, floating-leaved species were 18 and emergent species were 44 along elevation gradients in the three geographical divisions in Nepal. The Generalized Linear Model (GLM) was applied to find out the relation between the species richness of aquatic vascular macrophytes with elevation. It showed a statistically significant monotonic declining pattern with increasing elevation. The occurrence of this model was further verified by aquatic vascular macrophyte richness at every 200 m elevation which converged with the general pattern. The study conducted along one of the world’s longest bioclimatic elevational gradients led to support the monotonic declining pattern of aquatic vascular macrophytes richness indicating the difference in richness pattern among aquatic and terrestrial ecosystems. It also emphasizes the importance of conserving aquatic ecosystems with their vegetation.